2004
DOI: 10.1038/nrmicro974
|View full text |Cite
|
Sign up to set email alerts
|

Passive antibody therapy for infectious diseases

Abstract: Antibody-based therapies are currently undergoing a renaissance. After being developed and then largely abandoned in the twentieth century, many antibody preparations are now in clinical use. However, most of the reagents that are available target non-infectious diseases. Interest in using antibodies to treat infectious diseases is now being fuelled by the wide dissemination of drug-resistant microorganisms, the emergence of new microorganisms, the relative inefficacy of antimicrobial drugs in immunocompromise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
391
0
11

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 481 publications
(403 citation statements)
references
References 60 publications
1
391
0
11
Order By: Relevance
“…Antibodies are natural products of the immune system and interact with other immune components. Protective mAb may act through complement-mediated lysis, enhancement, or inhibition of phagocytosis, Fc-mediated cytokine release, and direct antimicrobial effects [19]. Our results showed that yeast cells opsonized with anti-70-kDa protein mAb had increased the phagocytic index.…”
Section: Discussionmentioning
confidence: 63%
“…Antibodies are natural products of the immune system and interact with other immune components. Protective mAb may act through complement-mediated lysis, enhancement, or inhibition of phagocytosis, Fc-mediated cytokine release, and direct antimicrobial effects [19]. Our results showed that yeast cells opsonized with anti-70-kDa protein mAb had increased the phagocytic index.…”
Section: Discussionmentioning
confidence: 63%
“…First, the corresponding mRNAs are matured and translated in the rough ER; then their nascent polypeptides are translocated into the ER and the N-terminal signal peptide is subsequently cleaved; folding is assisted by ER resident chaperones as the Immunoglobulin Heavy Chain Binding Protein (BiP) [37]. Besides, the Endoplasmic Reticulum Associated Protein Degradation (ERAD) quality control mechanism ensures that unfolded antibody chains are removed from the ER and degraded via the proteosome [38]. Finally, antibody chains are linked together by disulfide bonds established by ER-resident protein disulfide isomerase (PDI) [39].…”
Section: Deleted: Alsomentioning
confidence: 99%
“…Besides, the Endoplasmic Reticulum Associated Protein Degradation (ERAD) quality control mechanism ensures that unfolded antibody chains are removed from the ER and degraded via the proteosome [38]. Finally, antibody chains are linked together by disulfide bonds established by ER-resident protein disulfide isomerase (PDI) [39].…”
Section: Acknowledgementsmentioning
confidence: 99%
“…This technology allowed the production of large quantities of homogeneous antibodies of a single isotype in tissue culture and monoclonal antibodies became powerful agents in the treatment and diagnosis of diseases, as well as important research tools (Casadevall et al, 2004;Stacy, 2005). Since its inception, the major drawback of the hybridoma technology has been that it recovers only a tiny percent of the B cells that are making antibody to a particular antigen at the time of fusion.…”
Section: Introductionmentioning
confidence: 99%